2015
DOI: 10.1111/jomf.12143
|View full text |Cite
|
Sign up to set email alerts
|

Families Under the Microscope: Repeated Sampling of Perceptions, Experiences, Biology, and Behavior

Abstract: Questionnaires and laboratory observations have become so engrained in our research literature that it is easy to forget that neither family members' evaluations nor their behavior in situations structured by an investigator are necessarily the phenomena of interest. However, the study of life as it is actually lived is becoming more prominent in research on families. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 153 publications
(196 reference statements)
5
76
0
Order By: Relevance
“…Family researchers have begun applying ILM to basic family research (for a recent review see Repetti, Reynolds & Sears, 2015). Studies have reported good compliance and feasibility of ILM with a variety of samples including with parents and children; for example, a 56-day (two-month) protocol of five-minute daily diaries was feasible for parents and their 8–13 year olds (Robles, Reynolds, Repetti, & Chung, 2013).…”
Section: The Application Of Intensive Longitudinal Methods To Appliedmentioning
confidence: 99%
See 3 more Smart Citations
“…Family researchers have begun applying ILM to basic family research (for a recent review see Repetti, Reynolds & Sears, 2015). Studies have reported good compliance and feasibility of ILM with a variety of samples including with parents and children; for example, a 56-day (two-month) protocol of five-minute daily diaries was feasible for parents and their 8–13 year olds (Robles, Reynolds, Repetti, & Chung, 2013).…”
Section: The Application Of Intensive Longitudinal Methods To Appliedmentioning
confidence: 99%
“…The number and frequency of assessments in intensive repeated measures studies calls for frequent introspection and recall, which could result in participant reactivity (Repetti, Reynolds, & Sears, 2015; Bolger & Laurenceau, 2013). Reactivity results to the extent that participants are influenced by their own increased attention to and evaluation of the assessed constructs and respond by changing their behavior—such as decreasing or increasing the number of “events” they experience in event-contingent designs, or attempting to enact more personally acceptable behavior.…”
Section: The Application Of Intensive Longitudinal Methods To Appliedmentioning
confidence: 99%
See 2 more Smart Citations
“…These methods are useful because they capture family interactions, engage measurement proximal to the phenomena of interest (e.g., reduce recall bias), and provide for detailed study of inter-family differences in intra-family associations (Bolger, Davis, & Rafaeli, 2003; Repetti, Reynolds, & Sears, 2015). …”
Section: Intensive Longitudinal Data From Experience Sampling Studiesmentioning
confidence: 99%